1982
DOI: 10.1007/bf00257724
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adrenaline and noradrenaline concentrations in diabetic patients with and without autonomic neuropathy at rest and during sympathetic stimulation

Abstract: Summary. Plasma concentrations of adrenaline and noradrenaline were measured radio-enzymatically in nine patients with diabetic autonomic neuropathy, seven diabetic patients without autonomic neuropathy and nine normal subjects, in the recumbent position and after standing. Furthermore, in six patients with autonomic neuropathy and in the normal subjects, plasma noradrenaline and adrenaline concentrations were determined during and after cyclo-ergometer exercise. No differences in plasma adrenaline concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
3
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
3
12
3
1
Order By: Relevance
“…In spite of a marked increase of adrenaline concentrations the recovery from hypoglycaemia was slow following propranolol and bradycardia and ectopic beats were observed (Deacon et al, 1977). These results imply that propranolol treatment carries some risk in insulin-dependent diabetics (Kotler et al, 1966;Wright et al, 1979) who have reduced adrenergic responses due to autonomic neuropathy (Caviezel et al, 1980;Barnett et al, 1980 A, during insulin-(0.1 U/kg body weight) induced hypoglycaemia and after an oral glucose load (100 g) on heart rates in volunteers (n = 8). Mean ± s.e.mean results.…”
Section: Discussionmentioning
confidence: 91%
“…In spite of a marked increase of adrenaline concentrations the recovery from hypoglycaemia was slow following propranolol and bradycardia and ectopic beats were observed (Deacon et al, 1977). These results imply that propranolol treatment carries some risk in insulin-dependent diabetics (Kotler et al, 1966;Wright et al, 1979) who have reduced adrenergic responses due to autonomic neuropathy (Caviezel et al, 1980;Barnett et al, 1980 A, during insulin-(0.1 U/kg body weight) induced hypoglycaemia and after an oral glucose load (100 g) on heart rates in volunteers (n = 8). Mean ± s.e.mean results.…”
Section: Discussionmentioning
confidence: 91%
“…By design, our findings were obtained in patients with type 2 diabetes who had no evidence of neuropathy, because this could interfere with autonomic neural control and its effects [33][34][35][36]. We used previously accepted criteria [19,20], as well as clinical examination and vasopressor responses, to exclude somatic and autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 100 nonketotic diabetic patients, Cryer et al (23) showed mean basal and posturally stimulated plasma NE was normal, but subsets of neuropathic patients were identified as having exaggerated or reduced sympathoadrenal re • sponses. Caviezel et al (24) found basal and posturally stimulated NE to be reduced in diabetic patients who had autonomic and painless somatic neuropathy. Christensen (25) found plasma catecholamines to be reduced in diabetic patients with peripheral neuropathy in one study, whereas in another study he found no difference in plasma NE between neuropathic and nonneuropathic diabetic patients (26).…”
Section: Plasma Nementioning
confidence: 98%